Silk Fibroin for Flexible Electronic Devices - Zhu, Bowen; Wang, Hong; Leow, Wan Ru; Cai, Yurong; Loh, Xian Jun; Han, Ming-Yong; Chen, Xiaodong (Advanced materials (Weinheim), 2016)
Flexible electronic devices are necessary for applications involving unconventional interfaces, such as soft and curved biological systems, in which traditional silicon‐based electronics would confront a mechanical mismatch. Biological polymers offer new opportunities for flexible electronic devices by virtue of their biocompatibility, environmental benignity, and sustainability, as well as low cost. As an intriguing and abundant biomaterial, silk offers exquisite mechanical, optical, and electrical properties that are advantageous toward the development of next‐generation biocompatible electronic devices. The utilization of silk fibroin is emphasized as both passive and active components in flexible electronic devices. The employment of biocompatible and biosustainable silk materials revolutionizes state‐of‐the‐art electronic devices and systems that currently rely on conventional semiconductor technologies. Advances in silk‐based electronic devices would open new avenues for employing biomaterials in the design and integration of high‐performance biointegrated electronics for future applications in consumer electronics, computing technologies, and biomedical diagnosis, as well as human–machine interfaces. Silk fibroin is an ancient biomaterial with exquisite mechanical, optical, and electrical properties. Its intriguing properties and environmental benignity render silk fibroin compelling for the advancement of next‐generation biocompatible and biodegradable flexible electronic devices.